Prediktor Obesitas Sentral dan Korelasinya dengan Tekanan Darah Diastolik: Studi Observasional pada Populasi Lansia di Pedesaan - Aristawidya Dwi Rahmadevi; Sudrajah Warajati Kisnawaty; Nur Lathifah Mardiyati (INSOLOGI: Jurnal Sains dan Teknologi, 2025)
Hypertension is a major health problem among the elderly and is strongly associated with central obesity, which often increases due to physiological changes during aging. Waist circumference (WC) and waist-to-height ratio (WHtR) are recognized as practical anthropometric indicators for assessing central obesity and predicting cardiovascular risks, including elevated blood pressure. This study aimed to examine the relationship between waist circumference and waist-to-height ratio with systolic and diastolic blood pressure among elderly individuals in Cemani Village. This research employed an analytical observational design with a cross-sectional approach involving 69 elderly respondents selected through consecutive sampling. Data on waist circumference, height, and blood pressure were obtained through direct measurements. Statistical analysis was performed using Pearson or Spearman correlation tests based on normality results. The findings showed that most respondents had WC and WHtR values categorized as centrally obese. Waist circumference and WHtR were not significantly associated with systolic blood pressure (p = 0.794; p = 0.824), but both demonstrated significant associations with diastolic blood pressure (p = 0.002; p = 0.001). These results indicate that central obesity, reflected by WC and WHtR, may contribute more strongly to diastolic pressure elevation than to systolic changes. Therefore, routine monitoring of anthropometric indicators among the elderly is essential for early detection and prevention of hypertension.